Hallmark's Happy Crime Films. Issue 1 (2nd January 2022) - Braithwaite, Andrea
ABSTRACT: This article highlights the significance of the crime genre to the resurgence of the made-for-TV-movie, especially the Hallmark Channel's romance movies. Typical assessments of Hallmark movies as brimming with positive affect encourage us to take a closer look at the representational strategies that make such happiness possible in stories otherwise concerned with violence and death. I draw upon theories of melodrama and film to identify which experiences are considered common or shared in these predominantly white, upper-class worlds, and how they create an orientation against which guilt and justice are determined. I also situate these made-for-TV-movies in relation to discussions about the status of filmmaking in Canada, as examples of the distinct shift in emphasis in Canadian cultural policy that now sees cultural texts as products and prioritizes commercially viable—and internationally desirable—media (as distinct from "national cinema"). I combine these critical perspectives to track the ways in which Hallmark combines high body counts, low violence, and often White homogeneity into happy crime films—and what the mass production of them tells us about the present and future of filmmaking in Canada.